Effects of Social Determinants of Health on Stroke Survivor Discharge Location From an Acute Comprehensive Stroke Center - Migliarese, Sara; Adams, Tiffany; McCloskey, Kiran; Henao, David; Gregory, Chere (American journal of physical medicine & rehabilitation, 2025)
This study aimed to assess the influence of social determinants of health on discharge location after an acute care hospital admission due to stroke. Retrospective analyses assessed electronic medical records from an acute facility in North Carolina dating from November 20, 2014, to December 29, 2019 ( N = 4603). All subjects were diagnosed with stroke and received at least one physical therapy session. Multinomial stepwise logistic regression assessed the clinical and demographic factors associated with being discharged to each home care with services, skilled nursing facilities, or inpatient rehabilitation in comparison to home with self-care. After accounting for clinical variables, being younger, having a significant other, holding private insurance, being female, and being of Hispanic ethnicity were associated with a greater probability of being discharged to home with self-care. Compared to White patients, Black patients were more likely to be discharged to home care with services than home with self-care. Intraclass correlations indicated that zip code of residence may influence likelihood of being discharged to a skilled nursing facility. This analysis demonstrates that social determinants of health are associated with discharge location. Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME. Upon completion of this article, the reader should be able to: • Describe key demographic factors and social determinants of health that are associated with discharge disposition for patients leaving an acute facility after stroke; • Discuss potential mechanisms by which demographic factors and social determinants of health are associated with discharge disposition for patients leaving an acute facility after stroke; and • Identify areas where future research is needed to further understand mechanisms by which disparities in discharge disposition occur, or to reconcile disparate results. Advanced. The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians.The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity.